Review: Climate-induced hydrological changes and the ecology of tropical freshwater biota - SUNARDI SUNARDI; GERHARD WIEGLEB (Biodiversitas Journal of Biological Diversity, 2016)
Sunardi, Wiegleb G. 2016. Climate-induced hydrological changes and the ecology of tropical freshwater biota. Biodiversitas 17: 322-331. Climate change is believed to pose adverse effects to biodiversity of aquatic systems, with no exception of those in tropical areas. However, next few decades species extinction is suggested as dark future as we lack researches uncovering how climate change threats the aquatic biota. Unluckily, the tropical freshwater systems are expected to suffer more severe impacts of climate change, from heavy floods or extended drought than do the boreal areas. A comprehensive understanding of biota’ performance in face of climatic pressures, will guide the further necessary researches. This paper presents a review on the available researches addressing ecological effects of the most influential climatic parameter in tropic area, the hydrological regime, on freshwater biota. The research reveal that the extreme water fluctuations induced by climate change have negatively affected the performance of freshwater biota. In the next few decades, climate change seems to remain as one of the main threats for freshwater ecosystems, and is responsible for the lost of itsbiodiversity.